2012
DOI: 10.1002/cctc.201200365
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of a Carbon Black Supported PtAg Non‐Alloy Bimetal Nanocatalyst for CO Preferential Oxidation in Excess Hydrogen

Abstract: Carbon black (CB) supported PtAg non‐alloy bimetal catalysts were prepared by incipient wetness impregnation and evaluated for CO preferential oxidation in excess H2 (PROX). PtAg/CB catalysts exhibited an evident synergistic effect. The catalyst support selection is crucial to the synergistic effect. X‐ray diffraction (XRD), transmission electron microscopy (TEM), and scanning TEM energy dispersive X‐ray analysis (STEM‐EDX) characterization indicates no alloy was formed over the PtAg/CB catalyst after activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
6
0
2
Order By: Relevance
“…因此, 碳材料被广泛用作催 化剂载体. [13][14][15][16][17][18] 碳纳米管(CNTs), 因具有大的长径比、 较高的比表面积且机械强度大、 硬度大、 热稳定性 高 、 类 石 墨 的 管 壁 以 及 高 的 导 电 率 等 优 点, 常 被 用作 CO 和 CO2 加氢合成甲醇催化剂的载体或助 剂. 5,18-20 厦门大学的张鸿斌教授 5,19,20 以金属改性后的 CNTs 为催化剂助剂, 提高了 CO2加氢合成甲醇的反 应活性和选择性.…”
Section: 引 言unclassified
“…因此, 碳材料被广泛用作催 化剂载体. [13][14][15][16][17][18] 碳纳米管(CNTs), 因具有大的长径比、 较高的比表面积且机械强度大、 硬度大、 热稳定性 高 、 类 石 墨 的 管 壁 以 及 高 的 导 电 率 等 优 点, 常 被 用作 CO 和 CO2 加氢合成甲醇催化剂的载体或助 剂. 5,18-20 厦门大学的张鸿斌教授 5,19,20 以金属改性后的 CNTs 为催化剂助剂, 提高了 CO2加氢合成甲醇的反 应活性和选择性.…”
Section: 引 言unclassified
“…Besides, carbon surface chemistry also plays vital roles on the catalytic properties. [25][26][27] Our previous research demonstrated that carbon surface chemistry can inuence catalyst particle size and support-metal interactions remarkably, then modify the catalytic performance dramatically, especially for multi-component catalytic systems. The similar phenomena were also reported by other researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytic oxidation of formic acid (HCOOH) has attracted lots of attention in recent decades due to its relevance to developing efficient direct formic acid fuel cells (DFAFCs). [1][2][3][4][5][6][7][8][9] Pt and Pd noble metal nanoparticles supported commonly on various carbon materials such as carbon nanotubes [10][11][12][13][14] are known as the most effective anode catalysts for the oxidation of formic acid at the anode of DFAFCs. [15][16][17][18][19][20] Extensive investigations have been conducted to elucidate the mechanism of HCOOH electro-oxidation on the surfaces of various metals, including Pt, 15,[21][22][23] Pd, 13,20,24,25 Ru, 9,26,27 Au, 28,29 and Ni, 24,30 which have provided fundamental insights into the overall reaction pathways.…”
Section: Introductionmentioning
confidence: 99%